Докритический рост дискообразной трещины с немалой зоной предразрушения в стареющем трансверсально-изотропном теле - Каминский, A.A.; Гаврилов, Г.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We consider the long-term cracking of an aging transversally isotropic material containing a mode I penny-shaped crack with a non-small process zone under remotely applied tensile stress. Only the symmetric case, where the crack lies in the plane of isotropy, is considered. The aging material properties are described by the Boltzmann - Volterra's linear theory for integral operators with non-difference kernels. The modified Leonov - Panasyuk - Dugdale's crack model is used with a constant process zone assuming that the critical opening displacement is the fracture criterion. Numerical calculations are made for subcritical crack growth for the specific example of a transversally isotropic material simulating the behavior of reinforced concrete.